PERLINDUNGAN KEANEKARAGAMAN HAYATI DALAM HUKUM ISLAM - Muhammad SRP, Sri Gilang (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2016)
Biodiversity is one of the components of the environment which plays an important role in shaping the ecosystem that provides life support on Earth. For that reason, the efforts to provide protection is necessary. Islam is very much aware of the important role of biodiversity, therefore Islam have participated in biodiversity protection through Islamic law. The protection of biodiversity in Islamic law demonstrated by the various rules derived from the Quran, hadith and fatwas of the scholars as well as demonstrated by the existence of conservation institution known as Hima and Zone Harim. Indonesia as the country with the second greatest biodiversity in the world and a country with a largest Muslim majority population in the world have an important role to develop and utilize the Islamic legal tradition in the protection of biodiversity in the scope of the provisions of national in order to increase the participation of Muslims globally in protection and preservation activities of the environment, especially biodiversity.Keyword : protection, biodiversity, islamic law, hima, harim zone